Data Set for the Reporting of Endometrial Cancer: Recommendations From the International Collaboration on Cancer Reporting (ICCR). (24th November 2022) - Matias-Guiu, Xavier; Selinger, Christina I.; Anderson, Lyndal; Buza, Natalia; Ellenson, Lora H.; Fadare, Oluwole; Ganesan, Raji; Ip, Philip P.C.; Palacios, Jose; Parra-Herran, Carlos; Raspollini, Maria R.; Soslow, Robert A.; et al.
Abstract : Endometrial cancer is one of the most common cancers among women. The International Collaboration on Cancer Reporting (ICCR) developed a standardized endometrial cancer data set in 2011, which provided detailed recommendations for the reporting of resection specimens of these neoplasms. A new data set has been developed, which incorporates the updated 2020 World Health Organization Classification of Female Genital Tumors, the Cancer Genome Atlas (TCGA) molecular classification of endometrial cancers, and other major advances in endometrial cancer reporting, all of which necessitated a major revision of the data set. This updated data set has been produced by a panel of expert pathologists and an expert clinician and has been subject to international open consultation. The data set includes core elements which are unanimously agreed upon as essential for cancer diagnosis, clinical management, staging, or prognosis and noncore elements which are clinically important, but not essential. Explanatory notes are provided for each element. Adoption of this updated data set will result in improvements in endometrial cancer patient care.